2018
DOI: 10.17358/ijbe.4.2.109
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Quality, Communication and Outputs of Marketing Channel of Cianjur Pandanwangi Rice on Consumer Trust in Java West Marketing Area

Abstract: The objectives of this study are to examine: 1) the influence of product quality, marketing communications and marketing distribution outlet or output channel on consumer trust; 2) dominant factors that influence consumer trust in Cianjur Pandanwangi rice. A descriptive verification method was conducted in order to get an idea of the four dimensions of product quality, the four dimensions of marketing communications and the three dimensions of the marketing distribution channel in building consumer trust in Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…In addition, previous showed that interpersonal communication and social networks are able to strengthen the influence of the mass media, especially in which the public is unfamiliar enough with nanotechnology (Ho et al 2011). Consumer confidence is not only built from good product quality and ease of availability, but also from appropriate communication media reaching the right target (Lisarini et al 2018). The same analysis is also supported by previous research that has been done by Ho (2008) in which the study stated that the communication media have given significant effect on trust.…”
Section: The Effect Of Communication Media On Trustsupporting
confidence: 70%
“…In addition, previous showed that interpersonal communication and social networks are able to strengthen the influence of the mass media, especially in which the public is unfamiliar enough with nanotechnology (Ho et al 2011). Consumer confidence is not only built from good product quality and ease of availability, but also from appropriate communication media reaching the right target (Lisarini et al 2018). The same analysis is also supported by previous research that has been done by Ho (2008) in which the study stated that the communication media have given significant effect on trust.…”
Section: The Effect Of Communication Media On Trustsupporting
confidence: 70%
“…Almost all of those variations have excellent fragrances, except beras merah and burung naga. Some researchers mentioned that farmers are not really interested in planting pandan wangi because of some reasons mainly from lack of socialization from the local government and that the harvest cannot cover the initial price (Lisarini et al 2018;Supyandi et al 2019). By botanists, rice is grouped into two varieties: Oryza sativa japonica and Oryza sativa indica (Widjaja et al 2014).…”
Section: Ricementioning
confidence: 99%